2021
DOI: 10.1111/jonm.13427
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of workplace violence against nurses among Chinese hospitals: A meta‐analysis

Abstract: Aims To explore the incidence of workplace violence against nurses in Chinese hospitals. Background Previous systematic reviews on the incidence of workplace violence against Chinese health care workers did not include many articles published in Chinese. Although several studies have investigated cases of violence against health care providers in China, no meta‐analysis has been conducted to assess the incidence of violence against Chinese nurses. Evaluation In this study, relevant data were retrieved from stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
15
1
1
Order By: Relevance
“…According to Zhang et al (2021) , the performance of nurses has a significant impact on patient satisfaction and overall health. Chinese nurses are confronted with a variety of issues, including workplace violence ( Liu et al, 2021 ), as well as psychological and healthcare issues ( Cai et al, 2020 ). In high-power-distant societies, nurses require high moral leadership, kindness, and authoritativeness ( Ugurluoglu et al, 2018 ; Sungur et al, 2019 ; Saygili et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhang et al (2021) , the performance of nurses has a significant impact on patient satisfaction and overall health. Chinese nurses are confronted with a variety of issues, including workplace violence ( Liu et al, 2021 ), as well as psychological and healthcare issues ( Cai et al, 2020 ). In high-power-distant societies, nurses require high moral leadership, kindness, and authoritativeness ( Ugurluoglu et al, 2018 ; Sungur et al, 2019 ; Saygili et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was similar to the finding of the systematic review and meta-analysis conducted by Liu et al on workplace violence against nurses in Chinese hospitals, in which the prevalence of such crimes was 72% in the secondary hospitals. 29 Besides, regarding the prevalence of the crimes as workplace violence in other types of medical institutions, a study performed by Hasan et al also reported the similar results with more than one-third (39%) of the crimes as workplace violence in primary health care institutions and 39% of the crimes as workplace violence in tertiary medical institutions in Bangladesh. 30 Chen et al also found that the prevalence of the crimes as workplace violence in top-level hospitals was lower compared with other types in China.…”
Section: Discussionmentioning
confidence: 68%
“…The subjects who had experienced physical and verbal abuse during work hours negatively assessed occupational retention as they are susceptible to abuse arising from excessive workloads or negative relationships with patients, families, and colleagues. Approximately 63% of Chinese nurses and 74.3% of South Korean nurses reported having experienced verbal abuse (Chang et al, 2019; Liu et al, 2022), thereby decreasing occupational retention. The American Nurses Association and the Joint Commission have denounced verbal and physical violence and workplace bullying (American Nurses Association, 2019; The Joint Commission, 2019).…”
Section: Discussionmentioning
confidence: 99%